2021
DOI: 10.1177/17585732211032922
|View full text |Cite
|
Sign up to set email alerts
|

Early outcomes of augmented glenoid components in anatomic total shoulder arthroplasty: a systematic review

Abstract: Background The objective was to evaluate the short-term clinical and radiological outcomes following augmented anatomic total shoulder arthroplasty in patients with posterior glenoid deficiency. Methods An electronic search of EMBASE, MEDLINE, and PubMed identified studies reporting clinical and radiographic outcomes following augmented anatomic total shoulder arthroplasty among patients with posterior glenoid deficiency. Results Nine studies including 312 shoulders underwent anatomic total shoulder arthroplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Glenoid component augmentation is an additional method that has been described as a method of addressing glenoid bony defects during both anatomic TSA and RTSA. Augmented components include polyethylene designs utilized for anatomic TSA and are made of metal in baseplate components used in RTSA ( 22 - 24 ). Various augmented glenoid component designs have been described for anatomic TSA including all-polyethylene monoblock with full-wedge (Equinoxe; Exactech, Gainesville, FL, USA) ( 22 ), half-wedge augmented glenoid (Aequalis Perform+; Wright Medical Group, Memphis, TN, USA) ( 22 ), or step-cut design (Global StepTech; DePuy Synthes, Warsaw, IN, USA) ( 22 , 23 ) ( Figure 3 ).…”
Section: Surgical Techniques For Dealing With Glenoid Bone Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…Glenoid component augmentation is an additional method that has been described as a method of addressing glenoid bony defects during both anatomic TSA and RTSA. Augmented components include polyethylene designs utilized for anatomic TSA and are made of metal in baseplate components used in RTSA ( 22 - 24 ). Various augmented glenoid component designs have been described for anatomic TSA including all-polyethylene monoblock with full-wedge (Equinoxe; Exactech, Gainesville, FL, USA) ( 22 ), half-wedge augmented glenoid (Aequalis Perform+; Wright Medical Group, Memphis, TN, USA) ( 22 ), or step-cut design (Global StepTech; DePuy Synthes, Warsaw, IN, USA) ( 22 , 23 ) ( Figure 3 ).…”
Section: Surgical Techniques For Dealing With Glenoid Bone Lossmentioning
confidence: 99%
“…There are a number of clinical studies evaluating augmented glenoid components and augmented baseplates used in RTSA. A recent systematic review included nine studies (312 patients total) which used augmented glenoid components at a mean follow-up of 37 months (range, 2.3–72 months) ( 24 ). Overall, they found that 35% of patients had reported radiolucency surrounding the components with 44% rate of peg perforation in 5 mm augment stepped implants ( 24 ).…”
Section: Surgical Techniques For Dealing With Glenoid Bone Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Priddy et al 46 showed significantly higher degree of radiolucency around 16-degree augmented glenoids compared with 8-degree augments (p = 0.03), demonstrating there may be a limit to the degree of achievable augmentation without compromising implant stability. More recently, Sheth et al 50 published a systematic review and analysis of the available clinical literature. This included 9 studies with 312 shoulders who underwent TSA with an augmented glenoid component between 2015 and 2020.…”
Section: Augment Designs In Atsamentioning
confidence: 99%
“…The pooled complication rate was 2.6%, and the revision rate was 1.9% at short-term follow-up. It is important to note that all studies to date are retrospective in nature representing Level III or IV evidence 50 . Although these outcomes are promising and short-term complication rates are low, high-level studies with long-term follow-up are warranted.…”
Section: Augment Designs In Atsamentioning
confidence: 99%